2012
DOI: 10.1188/12.onf.e373-e379
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Pilot on Medication Adherence and Knowledge in Ambulatory Patients With Gastrointestinal Cancer

Abstract: he increase in development and approval of new oral cancer therapies has changed chemotherapy administration. That shift in the treatment paradigm has led healthcare professionals to address the need for the development of new models of care in patients receiving oral chemotherapy agents. Patients must now assume responsibility and control for selfadministration of those agents. Various factors that may be predictors of adherence to the prescribed regimen include patient perceptions; clinician beliefs; economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 32 publications
(33 reference statements)
1
26
0
4
Order By: Relevance
“…Patient education is the cornerstone of successful oral chemotherapy [8,15]. A feasibility pilot study of new medication adherence interventions suggests that nurses have an important role to play in education, monitoring, and follow-up [21]. A strong patient-nurse relationship is fundamental to individualized education, leading to successful management of and adherence to treatment regimens [4].…”
Section: Discussionmentioning
confidence: 99%
“…Patient education is the cornerstone of successful oral chemotherapy [8,15]. A feasibility pilot study of new medication adherence interventions suggests that nurses have an important role to play in education, monitoring, and follow-up [21]. A strong patient-nurse relationship is fundamental to individualized education, leading to successful management of and adherence to treatment regimens [4].…”
Section: Discussionmentioning
confidence: 99%
“…In a total of 12 studies ( [44][45][46][47], treatment monitoring [48], pharmacy-based programs [42,49,50], counseling programs [51,52], prefilled pill boxes [53], and automated voice response systems [54]. Five of these studies were randomized trials, none of which demonstrated significant differences between the intervention and control groups with respect to their primary adherence outcomes [44,45,47,52,54].…”
Section: Interventions To Improve Adherence To Oral Antineoplastic Thmentioning
confidence: 99%
“…One randomized, three-arm trial did show differences in adherence, favoring the intervention groups, when the investigators conducted a post hoc pooled analysis comparing both interventions to the control group [47]. The remaining investigations included two single-group studies (i.e., a feasibility pilot study [46] and a randomized crossover study [53]) and five investigations of nonrandomized observational cohorts with control groups [42,[48][49][50][51]. Of these investigations, only two nonrandomized cohort studies showed a significant benefit of their respective interventions for adherence to oral antineoplastic therapy relative to their control groups.…”
Section: Interventions To Improve Adherence To Oral Antineoplastic Thmentioning
confidence: 99%
See 1 more Smart Citation
“…In nursing, mHealth-based intervention studies are growing, such as a health outcome monitoring system for patients with cancer (Bielli et al, 2004), chemotherapy-related toxicity management (Maguire, McCann, Miller, & Kearney, 2008; McCann, Maguire, Miller, & Kearney, 2009), reminders for wearing sunscreen using text messaging (Armstrong et al, 2009), and behavioral coaching for patients with diabetes (Quinn et al, 2011). In the area of smoking cessation, text messaging interventions have demonstrated positive results in increasing short-term smoking cessation rates (Bélanger, Plotnikoff, Clark, & Courneya, 2012; Coleman & Pasternak, 2012; Karvinen, Raedeke, Arastu, & Allison, 2011; Sommers, Miller, & Berry, 2012). …”
Section: Introductionmentioning
confidence: 99%